Prayer : our deepest longing - Rolheiser, Ronald (Cincinnati, Ohio : Franciscan Media, 2013)
"Prayer: Our Deepest Longing looks at the issues facing people of faith in today's culture, and offers a way of more effectively dealing with them by seeking out opportunities for prayer. With simple, down-to-earth language, Rolheiser illustrates the importance of prayer and offers techniques on how to pray, using examples from daily life, Scripture, and contemporary writers. He delves into the places that we fear to go with our issues about prayer, encouraging us with gentle kindness and words of hope and inspiration. The book is divided into five sections. 1. Why Pray? Illustrates the purposes and benefits of prayer for ourselves, as well as for the broader Catholic community and even the world. 2. Why Is It so Hard? Notes how our contemporary culture conspires against taking time out for solitude and prayer, and how our own ego--with its fears, restlessness, and narcissism--can work against developing a deeper relationship with God through prayer. 3. What Is Prayer? Outlines the two basic types of prayer, that is, affective (personal) and priestly (for the world). This section also notes the many ways or methods for each type of prayer, such as meditation, contemplation, the divine office, the Mass, and Scripture. 4. Sticking with It When It Gets Hard. This section covers the development of mature prayer, discussing ways to pray in times of boredom, disillusionment, crisis, helplessness, or after a loved one's death. 5. Mysticism. Here we learn about this increasingly popular form of intimate relationship with God. There will be a leader's guide for this book, making it an ideal resource for use with prayer groups, small faith communities, and retreats. This is a book for all manner of believer, whether your faith is solidly rooted in Catholicism, wavering between the Christianity of childhood and non-participatory faith as an adult, or just not sure what you believe--or whether you believe at all. It addresses topics that typify our culture, such as narcissism, pragmatism, efficiency, and self-gratification, and that work against a healthy spiritual life. Finally, the book takes us to a place of contact and comfort, in relationship not only with God but with our true selves as well"--
"Prayer: Our Deepest Longing looks at the issues facing people of faith in today's culture, and offers a way of more effectively dealing with them by seeking out opportunities for prayer. With simple, down-to-earth language, Rolheiser illustrates the importance of prayer and offers techniques on how to pray, using examples from daily life, Scripture, and contemporary writers. He delves into the places that we fear to go with our issues about prayer, encouraging us with gentle kindness and words of hope and inspiration"--
Struggling in prayer -- Hearing God's voice in prayer -- Understanding priestly prayer -- Practicing affective prayer -- Growing to maturity in prayer -- Listening to God's heartbeat -- Resting in God's presence.
Includes bibliographical references.
Description based on print version record.
Keywords: Prayer -- Christianity; RELIGION / Prayer; RELIGION / Spirituality; RELIGION / Christianity / Catholic; Prayer -- Christianity; RELIGION / Christian Life / General; Electronic books